Pencegahan Gejala Depresi pada Lansia melalui Edukasi dan Deteksi Dini - Kusuma, Made Dian Shanti; Sari, Ni Made Candra Citra; Tripayana, I Nyoman (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Elderly people will face changes both physically and mentally. The changes that occur are generally decreased physical function, having comorbidities, and the emergence of symptoms of depression that are often not realized and detected due to the aging process. If symptoms of depression are not detected properly, it can cause the elderly to be at risk of depression. Efforts that can be made to prevent depression in the elderly are to routinely carry out early detection and provide mental health education. The purpose of this activity is to find out the elderly who have symptoms of depression and are at risk of depression. This activity was carried out in the Pedungan sub-district by involving assistance from the Health Center in the elderly posyandu program. The implementation of the activity was carried out for 2 weeks by involving the elderly who attended the elderly posyandu held in the hamlet/community of the sub-district. The measuring instrument used to conduct screening is the Geriatric Depression Scale-15 (GDS-15). This measuring instrument has been validated for application to the elderly. This community service activity was attended by 19 elderly people. There was an increase in knowledge scores before and after being given education. The results were analyzed using the Wilcoxon Signed Test with a p value <.001 and a Z value of -3.750. The difference in mean values ​​before education was 71.53 and after education was 80.16. The screening results showed that there were 6 (20.8%) elderly people who had symptoms of depression. Elderly people who have symptoms of depression are then advised to immediately consult with health workers as an effort to treat the symptoms of depression they have, so that the elderly can avoid depression. The implementation of this activity is expected to be implemented routinely so that it can identify elderly people who are at risk of experiencing depression.